International Trade of Romania in the Context of its Low Economic Potential - Ionel Bostan (CES Working Papers, 2016)
The study provides a view on Romanian economy in terms of its competitiveness and potential for sustaining an efficient foreign trade. After reviewing literature and the reports of prestigious institutions and bodies in the area, the author presents several elements providing an accurate image on current quantitative and qualitative parameters of Romanian foreign trade, the internal and foreign processes influencing it and its main trends. The theoretical, legislative and institutional background of the paper was developed earlier by the author in his monograph - "The legal and financial regime applicable to international foreign trade" published in 2008 by ArtPress Publishing House after Romania joined the European Union. In this study, however, the focus is placed on major changes that have occurred in Romania's foreign trade after it joined the European structures.
Keywords: A10; F10; F49; 330; import; export; intra-communitarian trade; competitiveness; trade balance